Hypocretin Receptor 2 Antagonism Dose-Dependently Reduces Escalated Heroin Self-Administration in Rats - Schmeichel, Brooke E (Neuropsychopharmacology, 2015)
The hypocretin/orexin (HCRT) system has been associated with both positive and negative drug reinforcement, implicating HCRT receptor 1 (HCRT-R1) signaling in drug-related behaviors for all major drug classes, including opioids. However, to date there are limited studies investigating the role of HCRT receptor 2 (HCRT-R2) signaling in compulsive-like drug seeking. Escalation of drug intake with extended access has been suggested to model the transition from controlled drug use to compulsive-like drug seeking/taking. The current study examined the effects of a HCRT-R2 antagonist, NBI-80713, on heroin self-administration in rats allowed short- (1 h; ShA) or long- (12 h; LgA) access to intravenous heroin self-administration. Results indicate that systemically administered NBI-80713 dose-dependently decreased heroin self-administration in LgA, but not in ShA, animals. Quantitative PCR analyses showed an increase in Hcrtr2 mRNA levels in the central amygdala, a stress-related brain region, of LgA rats. These observations suggest a functional role for HCRT-R2 signaling in compulsive-like heroin self-administration associated with extended access and indicate HCRT-R2 antagonism as a potential pharmacological target for the treatment of heroin dependence.